Uniaxial Pressure Induced Giant Piezoresistance Effect in Magnetoresistive Manganites - Sarkar, Prosenjit (Journal of Scientific Research, 2025)
The uniaxial pressure (P) dependence of electrical resistivity along the ab-plane and c-axis has been investigated in the single crystals of (Sm1-yNdy)0.52Sr0.48MnO3 for y = 0 and 0.3. At ambient pressure, the metal-insulator phase transition has been observed both for y = 0 and 0.3. With the application of external uniaxial pressure in the direction perpendicular to the c-axis of the crystal, the metal-insulator transition shifts towards lower temperature, while the transition temperature increases with pressure when it is applied parallel to the c-axis. This behaviour is quite different from that observed in the case of external hydrostatic pressure. The most remarkable thing about the present study is that a giant piezoresistance effect was observed in the vicinity of the metal-insulator transition for y = 0.3 crystal, which may be used for various technological applications.